The Prevalence of Prenatal Diabetes Mellitus in Rania City: Women with Polycystic Ovaries - Renas Mohamed; Rahela A. Rasul (Kufa Journal for Nursing Sciences)
Background: Those with polycystic ovarian syndrome, which is a marker of the illness, can develop gestational diabetes mellitus. The frequency of gestational diabetes mellitus in women with polycystic ovaries varies greatly today. The aim of this study was to investigate the concurrent occurrence of gestational diabetes mellitus due to the fact that a variety of additional variables have been associated with the incidence of the condition in women with polycystic ovarian syndrome.